Nurain covets ‘EYREC Green Technology Young Scientist Award’ - UMP, PNC
Universiti Malaysia Pahang (UMP)'s Faculty of Chemical & Natural Resources Engineering (FKKSA) undergraduate, Nurain Mohd Yusoff, coveted the “EYREC Green Technology Young Scientist Award” and a gold medal, at the International Engineering Invention & Innovation Exhibition (i-ENVEX) 2011, with her project entitled “Sustainable Production of Alternative Sweetener From Empty Fruit Bunch Using Membrane Bioreactor (Waste to Wealth)”.